Pengaruh Irigasi terhadap Pertumbuhan dan Produksi Kelapa Sawit - Evizal, Rusdi; Sari, Rina Yunika; Saputra, Hidayat; Setiawan, Kukuh; Prasmatiwi, Fembriarti Erry (Universitas Lampung, 2021)
Growth and yield of oil palm is largely determined by climatic conditions especially in the dry season. The purpose of this study was to determine the effect of planting date and irrigation in the dry season of 2015 on the growth and production of palm oil in 2016. The data collecting was conducted from June to October 2016 at a plantation company, Southern Lampung. Treatments were arranged by factorial (3x2) in randomized block design with 7 replications. The first factor was age categories consisted of mature trees planted 2001 (TD 2001), young trees planted 2009 (TM 2009), and young trees planted 2010 (TM 2010). The second factor was irrigation (no irrigation and with irrigation). The irrigation used was bulk irrigation with rotation of once in a weeks during dry season (September-October). Observed variables were number of broken frond, spear frond, dried frond, female inflorencence, and bunches yield. Data was analyzed by analysis of the variance (ANOVA), and the differences of the mean were analyzed by Tuckey at 5% level of significant difference. Irrigation decreased number of broken frond and dry frond. Irrigation increased fresh fruit bunch yield of certain months in current and next year. Age categories (young and mature) had no signicantly effect on number of bunch and fresh fruit bunch per tree. However there was interaction between age categories and irrigation on the average of bunch weight. Keywords : growth, oil palm, rainfall, water deficit, yield